Dynamics of Supporters and Inhibitors of Social Emotional Learning (SEL) Implementation by Teachers in Learning at SDN Rajek - Haryanto, Haryanto; Murniati, Ngurah Ayu Nyoman; Supandi, Supandi (Journal of Educational Sciences, 2026)
This research was motivated by an anomaly in the Education Report Card data at SDN Rajek, where the increase in teacher well-being (79.00) was not linear with the low level of student well-being (66.30). This phenomenon indicates a barrier to the transmission of positive emotions within the school climate. This research aims to formulate a solution model to convert teacher well-being into Social Emotional Competence (SEC), which impacts students. Using a qualitative case study method, data was collected through interviews, observations, and document review. The results introduce the "RSI-SEC Bridge" model, which integrates three main pillars: Resilience, Systemic Competence, and Instructional Competence. This strategy transforms teachers' personal capacities into emotionally charged pedagogical practices in the classroom. The study's conclusions confirm that high teacher well-being requires a structured implementation strategy to mitigate student academic stress and sustainably improve the school's safety climate. This model serves as a crucial bridge in ensuring that teacher well-being is internalized into meaningful learning for students.